Functional assessment of autologous bone marrow cell therapy, mononuclear fraction on Chronic Spinal Cord injury: An experimental animal model - Carvalho, Katherine Athayde Teixeira de; Vialle, Emiliano Neves; Moreira, Guilherme Henrique Gonçalves; Francisco, Julio César; Simeoni, Rossana Baggio; Guarita-Souza, Luiz Cesar; Olandoski, Márcia; Vialle, Luiz Roberto Gomes; Cunha, Ricardo Corrêa (Brazilian Journal of Transplantation, 2007)
The cell therapy using several cell types has been proposed to promote regeneration after spinal cord injury. Purpose: To assess functional effects of the autologous bone marrow cells, mononuclear fraction transplantation in the chronic spinal cord trauma. Methods: 70 adults, male Wistar rats were submitted to spinal cord contusion injury by Impactor, being assessed every 48 hours using the Basso, Beatie and Bresnahan locomotor rating scale. After 14 days, those animals with score ≤ 16 were randomly divided in two groups: Control (vehicle) versus Study (with parenchymal cell infusion), which were followed-up for 10 days. The bone marrow cells, mononuclear fraction (CD45+ e CD34-) were attained and isolated by puncture-aspiration of the bone-marrow and by density gradient (d= 1.077). Statistics Analysis: as to the percentage scores, comparisons were performed between groups: non-parametric Mann-Whitney test, and for the comparison into groups: non-parametric Wilcoxon test. Results: From 70 animals, 24 rats attained ≤ 16 scores, and were submitted to the therapy: Control group (n=11), and Study group (n=13). From these, 7 and 11, respectively, ended the research. The statistical analysis did not show any significance: p>.05 in both tests. Conclusion: The bone marrow cell therapy, mononuclear fraction had not shown functional effectiveness in chronic spinal cord injury in this model.